To stand, belong and flourish : exploring the belonging and success of of Aotearoa university students : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Palmerston North, Manawatū, New Zealand - Ngata-Turley, Courtney (Massey University, 2021)
A sense of belonging has been described as a fundamental motivation for humans to feel accepted, valued and recognized by others and groups. While the importance of the need to belong has been extensively demonstrated throughout psychological literature, the importance of belonging in higher educational contexts – like universities – is not as clearly understood. Current research has shown that the stronger a student's sense of belonging is to their institution, the more likely they are to be successful in their academic achievement. However, the degree to which belonging plays a role in in this, especially in an Aotearoa context, is unknown, as well as the lack of student voice in psychological literature, leading to the question of what students define as success. A particular group of university students who are more commonly associated with the concept of belonging are those who are first in their family to attend university. These students often face unique challenges when entering university when compared with their counterparts, with connection, belonging, and relationship satisfaction being identified as key protective factors in the retention of first generation students. The current study explored the relationship between university belonging and student success through the experiences of First in the Family (FIF) and non-First in the Family (non-FIF) students. Two-hundred and thirteen Massey University undergraduate students completed an online questionnaire which measured their perceptions of academic success and feelings of belonging at university. This research found a significant and positive relationship between students' feelings of belonging and their feelings of university success. That is, the greater a student's sense of belonging to their university, the greater their feelings of academic success at university. It also found that students held multiple understandings of what success at university meant to them, as well as no overall significant difference in First in the Family and non-First in the Family experiences of belonging at university. The findings of this research will contribute to the sparse literature on university belonging and will provide an alternative pathway of understanding the concept, and will provide insight into how students define success at university.
Keywords: 520104 Industrial and organisational psychology (incl. human factors)